2016
DOI: 10.1160/th15-12-0987
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human soluble thrombomodulin and mortality in sepsis-induced disseminated intravascular coagulation

Abstract: SummaryRecombinant human soluble thrombomodulin (rhTM) is a novel class of anticoagulants for treating disseminated intravascular coagulation (DIC). Although rhTM is widely used in clinical settings throughout Japan, there is limited clinical evidence supporting the use of rhTM in patients with sepsis-induced DIC. Furthermore, rhTM is not approved for DIC treatment in other countries. This study aimed to clarify the survival benefits of rhTM administration in critically ill patients. Data from 3,195 consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 96 publications
(107 citation statements)
references
References 35 publications
3
104
0
Order By: Relevance
“…3). 20 These results revealed that rhTM administration was associated with reduced in‐hospital mortality among patients with sepsis‐induced DIC.…”
Section: Recombinant Human Soluble Thrombomodulinmentioning
confidence: 86%
See 3 more Smart Citations
“…3). 20 These results revealed that rhTM administration was associated with reduced in‐hospital mortality among patients with sepsis‐induced DIC.…”
Section: Recombinant Human Soluble Thrombomodulinmentioning
confidence: 86%
“…The survival rate was higher in the rhTM group than in the control group. Cited as Figure 3 in our previous report 20…”
Section: Recombinant Human Soluble Thrombomodulinmentioning
confidence: 99%
See 2 more Smart Citations
“…This retrospective observational study (Japan Septic Disseminated Intravascular Coagulation [JSEPTIC DIC] study) reviewed information obtained from patients who were admitted to 42 intensive care units (ICUs) at 40 institutions throughout Japan to undergo treatment of severe sepsis or septic shock between January 2011 and December 2013 10. The JSEPTIC DIC study was approved by the institutional review board at each hospital, and the requirement for informed consent was waived because of the retrospective design.…”
Section: Methodsmentioning
confidence: 99%